Effect of Planting Geometry and Seed Treatment on Growth and Yield of Wheat (Triticum aestivum L.) under System of Wheat Intensification - Haque, M.; Roy Chowdhury, A.; Acharya, S. S.; Ghosh, M.; Kumar, Sanjay; Kumar, Nikhil (International Journal of Bio-resource and Stress Management, 2015)
A field experiment was conducted during rabi season of 2011-12 and 2012-13 at Bihar Agricultural college, Sabour, Bhagalpur, Bihar, to study the effect of planting geometry and seed treatment on growth and yield of wheat under System of Wheat Intensification. The results indicated that maximum grain yield of wheat i.e., 48.71 and 51.17 q ha-1 during 2011-12 and 2012-13, respectively were recorded when the crop was sown in a fashion of 15×15 cm2 planting geometry which was significantly higher than the grain yield recorded under conventional and 10×10 cm2planting geometry but was at par with that obtained under the 20×20 cm2 planting geometry. It was also observed that grain yield of wheat was significantly higher with treated seeds i.e., 44.55 and 47.41 q ha-1 during 2011-12 and 2012-13 respectively, as compared to that obtained with untreated seed. With respect to grain yield, the treatment 15×15 cm2 geometry registered highest % increment in grain yield, having values 16.6% and 14.8% followed by 20×20 cm2 with values 11.4% and 7.7% in 2011-12 and 2012-13 respectively, over conventional sowing, the % increase in B:C ratio also followed the same trend during both the years of experimentation.